Mental imagery skill predicts adults' reading performance. (August 2022) - Suggate, Sebastian; Lenhard, Wolfgang
Abstract: Mental imagery is foundational to human experience, lying at the heart of cognition and reading, however research has failed to conclusively investigate and demonstrate a link. Therefore, we conducted three studies measuring adults' reading and imagery performance. In Study 1, the mental imagery skills of 155 adults were measured using two established self-report measures, namely the Plymouth Sensory Imagery Questionnaire (Psi-Q) and the Spontaneous Use of Imagery Scale (SUIS), and a novel imagery comparison task. In Study 2 ( n = 452), a control for speeded processing replaced the SUIS. In Study 3 ( n = 236), we added a measure of reading speed. Findings indicate that the objective measurement of mental imagery was associated with reading performance, whereas self-report measures were not. Further, reading comprehension linked more strongly to mental imagery than reading speed did. Findings demonstrate, for the first time, that mental imagery processes are intrinsically linked with reading performance. Highlights: Mental imagery uniquely predicted reading comprehension performance across three experiments. Links between reading and mental imagery were not explained by processing speed. A novel and objective measure of mental imagery proved superior to self-report measures. Mental imagery also appeared to relate to reading fluency.